2017
DOI: 10.1007/s10509-017-3059-2
|View full text |Cite
|
Sign up to set email alerts
|

Charged compact stellar model in Finch-Skea spacetime

Abstract: In this paper a compact charged stellar model in the Finch and Skea background spacetime [{\it Class. Quantum Gravity} {\bf6}, 467 (1989)] is presented. The model has been developed by assuming a particular charge distribution within the stellar interior. The model is well behaved and can describe a large class of compact stars. Physical features of the model are studied and in particular we show how the presence of charge can have a non-negligible impact on the mass-radius ($M-R$) relationship of such class o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 91 publications
2
6
0
Order By: Relevance
“…(13). Our study reconfirms [25] earlier claims that electric field and/or anisotropy can serve as tuning parameters to fine-tune the mass-radius relationship of compact stars.…”
Section: Physical Viabilitysupporting
confidence: 89%
“…(13). Our study reconfirms [25] earlier claims that electric field and/or anisotropy can serve as tuning parameters to fine-tune the mass-radius relationship of compact stars.…”
Section: Physical Viabilitysupporting
confidence: 89%
“…Consequently, for a given central and/or surface density, an external observer sees no change in its mass-radius relationship. In a separate study (Ratanpal et al (2017)) it has been observed that in the presence of an electric field a stellar configuration tends to accommodate more mass. However, it should be stressed that incorporation of an electromagnetic field changes the exterior spacetime from Schwarzschild to Reissner-Nordström whereas in our case the exterior spacetime remains unaltered.…”
Section: Physical Analysismentioning
confidence: 94%
“…The original Finch-Skea stellar model as well as the charged stellar model developed by Hansraj and Maharaj (2006) can be regained from the new class of solutions. For a specific charge distribution, Ratanpal et al (2017) obtained a new class of solutions in terms of Bessel functions for a matter distribution in the Finch-Skea background spacetime. The physically viable solution has been utilized to study the impact of charge on the mass-radius (M − R) relationship, in particular.…”
mentioning
confidence: 99%
“…By relaxing the pressure isotropy condition, Sharma et al (2017) generalized the Finch and Skea (1989) stellar model. For a specific charge distribution, Ratanpal et al (2017) also made a generalization of the Finch and Skea stellar model to analyze the impact of the charge on the mass-radius relationship of a compact star, in particular. The relativistic stellar model of Mak and Harko (2004) was extended by to include charge into the system.…”
Section: Introductionmentioning
confidence: 99%